Slow and steady...? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
By November 2002, the price of coffee has risen to its highest level in 2 years. The composite indicator price an average of various coffees traded on various markets reached US$ 0.50/lb, compared to US$ 0.42 in August, despite the continuing...